2022
DOI: 10.1371/journal.ppat.1010453
|View full text |Cite
|
Sign up to set email alerts
|

Reduced IRF4 expression promotes lytic phenotype in Type 2 EBV-infected B cells

Abstract: Humans are infected with two types of EBV (Type 1 (T1) and Type 2 (T2)) that differ substantially in their EBNA2 and EBNA 3A/B/C latency proteins and have different phenotypes in B cells. T1 EBV transforms B cells more efficiently than T2 EBV in vitro, and T2 EBV-infected B cells are more lytic. We previously showed that both increased NFATc1/c2 activity, and an NFAT-binding motif within the BZLF1 immediate-early promoter variant (Zp-V3) contained in all T2 strains, contribute to lytic infection in T2 EBV-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 94 publications
4
16
1
Order By: Relevance
“…1e, S1f). Consistent with previous reports (33,34), GP350 + LMP1 hi cells highly expressed host NFATC1, MIER2, SFN and SGK1 genes and were the highest expressors of host box-dependent myc-interacting protein 1 (BIN1). Conversely, GP350 -LMP1 hi cells had the highest expression of host genes HSPB1, ABCB10, MALAT1 and CD44 (Fig.…”
Section: Single Cell Rna-sequencing Analyses Resolve Lcls Into Three ...supporting
confidence: 92%
See 2 more Smart Citations
“…1e, S1f). Consistent with previous reports (33,34), GP350 + LMP1 hi cells highly expressed host NFATC1, MIER2, SFN and SGK1 genes and were the highest expressors of host box-dependent myc-interacting protein 1 (BIN1). Conversely, GP350 -LMP1 hi cells had the highest expression of host genes HSPB1, ABCB10, MALAT1 and CD44 (Fig.…”
Section: Single Cell Rna-sequencing Analyses Resolve Lcls Into Three ...supporting
confidence: 92%
“…Consistently, a recent study has found that IRF4 knockdown in LCLs induces EBV lytic reactivation in LCLs and lytically infected cells have increased NFATc1 and decreased IRF4 expression (34). Collectively, our data suggest that SE-regulated genes are less highly expressed in GP350 + LMP1 hi LCLs, which show evidence of lytic EBV reactivation, and that experimental induction of EBV lytic cycle also represses expression of these genes.…”
Section: Gp350 -Lmp1 Lo Lcls Have Distinct Myc-dependent Transcriptio...supporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Table 1 , comparison of cellular gene expression in the T1 Akata virus-infected NOKs versus T2 AG876 virus-infected NOKs reveals 85 genes were significantly upregulated, and 36 genes significantly downregulated, in the Akata versus AG876 virus infected cells. In contrast, we previously found that close to 600 cellular genes were expressed at significantly different levels in T1 versus T2 EBV-infected lymphoblastoid B cell lines [ 29 ]. The AG876 virus-infected and Akata virus-infected NOKs are much more similar to each other compared to the uninfected NOKs.…”
Section: Resultsmentioning
confidence: 96%
“…The EBV transcript analysis of the RNA-seq results does not suggest that AG876 virus-infected and Akata virus-infected NOKs are significantly different in their ability to spontaneously lytically reactivate. However, given our recent finding that T2 EBV is more lytic than T1 EBV in lymphoblastoid B cell lines and in lymphomas of humanized mice [ 27 , 29 ], we explored whether T1 Akata virus-infected versus T2 AG876 virus-infected NOKs differ in their ability to switch to the lytic form of viral reactivation when treated with the phorbol ester TPA, suspended in methylcellulose, or rafted. The Kenney and Mertz labs have previously shown that the ability of TPA to induce lytic EBV reactivation of Akata virus-infected NOKs is at least partially dependent upon differentiation activated transcription factors such as BLIMP1 and KLF4 [ 12 , 44 ].…”
Section: Resultsmentioning
confidence: 99%